The international division of labour, local resources and engineering workers: Eastern Europe in the global networks of the semiconductor Industry. (1st October 2012) - ,
Abstract : The decades-long internationalisation of the semiconductor industry has been characterised by dynamics that do not easily fit into logics of centrality and peripherality, pointing to the fact that complementary divisions of labour are not the end of the process but mark its beginning. This article revolves around two case studies of design centres in Eastern Europe, focusing on the work of engineers as well as the upgrading of processes at the design centre level. This locally-centred and historical perspective makes it possible to depict internationalisation and integration into the global design networks of the semiconductor industry as a complex dialectical interaction between the global and the local.